Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1515/cclm-2018-1111
|View full text |Cite
|
Sign up to set email alerts
|

Making new biomarkers a reality: the case of serum human epididymis protein 4

Abstract: Background Measurement of human epididymis protein 4 (HE4) in serum has recently been proposed for clinical use in the framework of ovarian cancer (OvCa). We sought to retrace the translational phase and the clinical implementation steps boosting HE4’s clinical value and discuss the effects of its introduction on the diagnostic and management pathways. Methods Meta-analyses of running evidence have preliminarily suggested that HE4 may overcome carbohydrate antigen 125 (CA125) in identifying OvCa, showing howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 67 publications
(99 reference statements)
0
14
1
Order By: Relevance
“…For HE4 staining of TMAs, of the 26 clear cell RCC patients, only one (3.8%) was weakly positive and all others were negative for HE4 staining, although the percentage of strongly positive staining was very high for serous ovarian cancer, endometrial cancer and lung adenocarcinoma (81%, 49% and 33%, respectively.) in which cancers HE4 expression in tumor was reported as cancer biomarker [8][9][10][11][12]. Even in our study, the expression rate of HE4 in tumor tissue was very low in clear cell RCC (9.5%).…”
Section: Discussioncontrasting
confidence: 58%
“…For HE4 staining of TMAs, of the 26 clear cell RCC patients, only one (3.8%) was weakly positive and all others were negative for HE4 staining, although the percentage of strongly positive staining was very high for serous ovarian cancer, endometrial cancer and lung adenocarcinoma (81%, 49% and 33%, respectively.) in which cancers HE4 expression in tumor was reported as cancer biomarker [8][9][10][11][12]. Even in our study, the expression rate of HE4 in tumor tissue was very low in clear cell RCC (9.5%).…”
Section: Discussioncontrasting
confidence: 58%
“…Diagnostic accuracy of human epididymis secretory protein 4 for lung cancer: a systematic review and meta-analysis Human epididymis secretory protein 4 (HE4) has been regarded as a tumor marker for ovarian cancer for a long time (9,10). Interestingly, several studies have revealed that it is also a useful diagnostic marker for lung cancer (11)(12)(13), but the results of these studies are heterogeneous.…”
Section: Original Articlementioning
confidence: 99%
“…The disease dissemination score showed prognostic value in a previous study [24]. Patients were divided into a low tumor load group (dissemination score 0-12) and a high tumor load group (dissemination score [13][14][15][16][17][18][19][20][21]. In all patients treated with NACT, the disease dissemination score was calculated at diagnostic laparoscopy, before the initiation of chemotherapy.…”
Section: Study Populationmentioning
confidence: 99%
“…The shortcomings of CA125 and the insidious nature of HGSC have sprouted comprehensive research on more satisfactory biomarkers in the diagnosis, treatment monitoring, and follow up of the disease [12]. Human epididymis protein 4 (HE4) was first described by Kirchhoff et al [13], and it has since been proposed as a complement to CA125 in the diagnosis of HGSC [14].…”
Section: Introductionmentioning
confidence: 99%